(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Unfortunately, recent events have painted a bleak picture for Muslim women in India. Muslimwomen are being singled out as ’easy targets’ due to the increase of militant Hindu extremism. Thepresent problem of hate apps being created by young and educated people propagating hatred anddamaging the image of Muslim women reflects the bleak truth of their condition in India. Muslim Islamicdogma has further compounded their suffering by denying them basic human rights. They are victims ofwhat Kimberle Crenshaw has termed inter-sectionality since they are discriminated against for beingboth Muslim and female.Women’s status is often seen to be a reflection of their relative access to and control over the family’sand community’s financial and social capital, such as food, money, property, and other forms of wealth.From the perspective of a Muslim woman, all of these variables seem blurry because of the manyobstacles in the way. Comparing the status of Muslim women in India to that of Muslim women in Turkey,Iran, Saudi Arabia, and Afghanistan, this dissertation seeks to give a critical and theoretical examinationof the role of women in Islam as espoused by the Quran and Hadith. It investigates the constitutionalityof Personal law and the socioeconomic status of Muslim women in India. The article draws theconclusion that Muslim women, as a minority within a minority, are nonetheless compelled to lead areclusive and subservient lifestyle. Muslim women are among the most economically impoverished,politically marginalized, and educationally excluded demographic in the nation, as detailed in the SacharCommittee Report. Despite the fact that the Supreme Court of India has ruled that secular law applies toMuslims in the case of Shah Bano, personal law continues to flout constitutional guarantees ofnondiscrimination and equal treatment. The state and Islamic fundamentalists must come to their sensesand work together to ensure that the many programs and regulations designed to empower Muslimwomen are really put into practice.